Psychological factors influencing public perception of space tourism - Freitas, Laura Isabel Pereira de (2025)
Space tourism represents a novel yet underexplored frontier of leisure travel shaped by public perceptions. This study aims to identify psychological factors influencing tourist behavioral intention (TBI), by the mediating role of tourist stickiness. The study employed text mining techniques and Partial Least Squares-Structural Equation Modelling (PLS-SEM) to analyze 15,568 comments from the top 10 YouTube videos relevant to space tourism. The generated word frequency matrix (WFM) served as input for PLS-SEM to test the hypothesized relationships. The results showed that perceived feasibility and social status significantly increased tourist stickiness. While self-actualization had no significant effect. Tourist stickiness emerged as a key mediator linking these motivations to TBI, highlighting the importance of confidence in technology and social prestige over intrinsic personal growth. The proposed framework offers novel contributions to space tourism literature and provides actionable guidance for industry stakeholders to improve public engagement.